Life values of students of physical education as an element of their educational competence - Anna Brojek; Maria Anna Turosz; Anna Bochenek (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Values are standards of our thoughts, attitude and behaviour, defining who we are, the way we live and our functioning in interpersonal relations. Every man needs in his everyday life a signpost in the form of a specific system of standards and rules of conduct called values, which promote the development and, at the same time, protect against erroneous attitudes. In this situation, of particular importance are pedagogical competences of the teacher, who, besides educational and organizational tasks, should become a person who develops personality of a young man by teaching him values. Objective of the study was to investigate the value preferred by students of physical education and their goals and attitudes to life. The research was carried out by the diagnostic survey using the Milton Rokeach Scale Values and the questionnaire of our own design. Among the values cherished by the respondents, the final top positions were: health, mature love and respect for each other. Among the most highly rated values by the respondents there are honesty, ambition, willingness to love, responsibility, self-reliance and perseverance. Whereas the most important goals and aspirations in life among the respondents are: health, performing satisfactory work and reciprocated love.